ChemInform Abstract: A Combination of Copper(0) Powder and Selectfluor Enables Generation of Cationic Copper Species for Mild 1, 2‐Dicarbonylation of Alkynes. Issue 19 (13th May 2014) - Zhang, Wenxia; Zhang, Jian; Liu, Yunkui; Xu, Zhenyuan
Abstract The 1, 2‐dicarbonylation of alkynes with water and air as sources of oxygen is catalyzed by a cationic copper species generated in situ from copper powder and selectfluor.